Reference percentiles for evaluating phase angle using bioelectrical impedance analysis in Chinese children aged 6–11 years - Yang, Jiongxian; Qian, Yue; Gu, Xiping; Li, Yue; Yang, Chenlu; Liang, Aimin (Frontiers in Nutrition, 2025)
BackgroundBioelectrical impedance analysis (BIA)-derived phase angle (PhA) is influenced by multiple factors including age, sex, ethnicity, and growth status. However, reference ranges for PhA in Chinese children remain undefined. This study was designed to establish normative PhA values in Chinese school-aged children, with the goal of providing clinicians with more accurate nutrition assessments.MethodsA retrospective analysis was performed. Primary diagnosis reports were gathered from the hospital information system (HIS). The data were stratified by age and sex, with 95% confidence intervals (CIs) calculated for each demographic subgroup. Age- and sex-specific percentile curves were subsequently generated. A multivariable linear regression model was employed to examine the associations between PhA and potential determinants, including age, sex, body mass index (BMI), and other clinically relevant covariates.ResultsA total of 1,247 children were included in this study, with 689 (55.3%) being boys. No significant differences in PhA were detected between boys and girls in the 6- and 7-year-old age groups. However, boys consistently exhibited higher PhA values than girls in the 8–11-year-old age groups (p < 0.05). PhA increased with age in both sexes, with similar age-related trends and percentile curves. The regression model revealed that age (B = 0.018, 95%CI: 0.003, 0.033) and BMI (B = 0.077, 95%CI: 0.068, 0.086) were positively correlated with PhA, whereas extracellular water (ECW) / intracellular water (ICW) (B = −22.925, 95%CI: −25.150, −20.699) had a negative effect on PhA.ConclusionThis study delineates the characteristics of PhA in Chinese children aged 6 to 11 years. The newly established reference ranges offer clinicians and researchers a practical tool for evaluating PhA in this pediatric population. These findings provide a valuable foundation for clinical assessment and further research on PhA in children.